INTELLECTUAL CAPITAL AS A DRIVER OF ECONOMIC DEVELOPMENT - Sandra Jednak; Veljko Dmitrović; Vesna Damjanović (Economic Review)
There are different factors for obtaining economic development. In contemporary economics, knowledge and intellectual capital have become necessary for achieving economic development. Management and development of intellectual capital bring benefits and advance the economy. The main aim of the paper is to present the concept of intellectual capital as a driver of economic development. Selected indicators for measuring intellectual capital and knowledge and their influence on the economic development have been presented. The impact of intellectual capital on economic development is different based on the level of national economy development. Intellectual capital is a driver of economic development in advanced economies, while in developing countries it is not so dominant.